Monte Carlo techniques in radiation therapy: applications to dosimetry, imaging, and preclinical radiotherapy - Seco, Joao; Verhaegen, Frank (Imaging in medical diagnosis and therapy, 2022)
"Thoroughly updated throughout, this second edition of Monte Carlo Techniques in Radiation Therapy: Applications to Dosimetry, Imaging, Preclinical radiotherapy, edited by Joao Seco and Frank Verhaegen, explores the use of Monte Carlo methods for modelling various features of international and external radiation sources"--